Jacob's wealt h an examination into the nature and role of material possessions in the Jacob-cycle (Gen 25:19-35:29) - Vrolijk, Paul. (Vetus Testamentum, Supplements, 2011)
Various biblical studies on wealth and poverty have been published over the last thirty years. Some of these studies touch on the wealth of the patriarchs in Genesis 12-50, but they focus predominantly on other parts of the Bible. Scholars who have studied the patriarchal narratives in detail comment on aspects of patriarchal wealth, but do not offer an in-depth analysis of this topic. This book on Jacob's wealth shows that such an analysis is warranted. In the Jacob story, material possessions and their associated attitudes and actions are essential to understand the various relationship dynamics. Often, possessions are the cause of conflict, but they also play a role in conflict resolution. As a result, this study contributes to a fuller understanding of the Jacob-cycle.